Construct validity and reliability of Malay language-perception towards smoking questionnaire (BM-PTSQ) among secondary school adolescents - Lim, Jia Hui; Lim, Kuang Hock; Sumarni Mohd Ghazali,; Heng, Pei Pei; Cheong, Yoon Ling; Lim, Hui Li; Kee, Chee Cheong; Goh, Yee Lin; Ng, Khuen Yen (Penerbit Universiti Kebangsaan Malaysia, 2022)
Multitude studies have demonstrated that perception is an integral factor associated with smoking. However, no such tool was available in the Malay language. In this study, we established a Bahasa Malaysia version of PTSQ (BM-PTSQ) and tested the validity and reliability among secondary school adolescents. The English version of PTSQ originally consists of 12 items. It was translated into Bahasa Malaysia and back-translated again into English to check for consistency. After face validity (face-to-face query) was determined among 20 secondary school adolescents, only 10 items were included in the survey. Construct validity was established from 407 school adolescents through random selection in the same locality. More than 60% of the respondents were female, while the majority of them (67.3%) were schooling in rural areas. Then, the reliability of the questionnaire was determined with Cronbach’s alpha. The Exploratory Factor Analysis (EFA) has grouped PTSQ into two components associated with either knowledge or attitude towards smoking. The variance and Cronbach’s alpha for the first and second components were 38.24% and 0.861 (7 items), 21.62% and 0.661 (3 items), respectively. The PTSQ showed good validity and reliability for measuring perception of smoking among secondary school-going adolescents in Malaysia. Hence, this is a viable measurement tool. But, more importantly, this study showed an urgent need to improve smoking education among adolescents in Malaysia.